Usage Of Focused Assessment with Sonography in Trauma (Fast) Scan in Blunt Intraabdominal Trauma - Choon, Lee Kee (2020)
Background Blunt intra-abdominal trauma (BAT) encompasses a major portion of trauma cases in the emergency department (ED). It poses a difficulty in diagnosis due to its low sensitivity and specificity of history and physical examination. Morison pouch is typically considered the most common area of free fluid (FF) in BAT visualized on the focused assessment with sonography in trauma (FAST) scan. However, no studies to date have investigated the correlation of the abdominal quadrant for positive FF with the type of abdominal trauma. This study aims to determine the most common quadrant and subquadrants for detecting FF and their association with the type of injury in BAT patients. Methods This multicenter study evaluated 86 BAT patients who presented to the ED. The FAST scan was performed per trauma life support protocol, and video clips were extracted for patients with positive FAST findings confirmed by abdominal computed tomography (CT) or exploratory laparotomy. The most common quadrant and subquadrant positive for FF were then determined. Positive quadrants and their association with type of injury were also analyzed. Areas studied were the right upper quadrant (RUQ), left upper quadrant (LUQ), and suprapubic area (SP). Subquadrant areas were RUQ 1–hepato-diaphragmatic; RUQ 2–Morison pouch; RUQ 3–caudal liver edge and superior para-colic gutter; LUQ 1–splenicdiaphragmatic; LUQ 2–spleno-renal; LUQ 3–around the inferior pole of kidney; SP 1–bilateral to bladder; SP 2–posterior to bladder; and SP 3–posterior to uterus. Results The most frequent region with positive FF results was the RUQ, seen in 82 (95.3%) patients. In subquadrant analysis, RUQ 3 was the most common region (78 patients, 90.75%), followed by RUQ 2 (73 patients, 84.9%) and LUQ 2 (51 patients, 59.3%). A significant association was observed between the LUQ region positive for FF and the presence of splenic injury (p = 0.006). Conclusion In patients with BAI, the RUQ is the most frequent quadrant and RUQ 3 is the most frequent subquadrant positive FF. A positive LUQ free fluid suggests the presence of splenic injury in BAT.